Institutional communication revisited: Preferences, opportunity structures and scientific expertise in policy networks - Philip Leifeld; Volker Schneider (Max Planck Institute for Research on Collective Goods, 2010)
Information exchange in policy networks is usually attributed to preference similarity, influence reputation, social trust and institutional actor roles. We suggest that political opportunity structures and transaction costs play another crucial role and estimate a rich statistical network model on tie formation in the German toxic chemicals policy domain. The results indicate that the effect of preference similarity is absorbed by other determinants while opportunity structures indeed have to be taken into account. We also find that different types of information exchange operate in complementary, but not necessarily congruent, ways.
Keywords: 330; Chemikalienrecht; Interessenpolitik; Netzwerk; Informationsaustausch; Präferenztheorie; Opportunismus; Transaktionskosten; Schätzung; Deutschland